The effect of family supportive supervisor behavior on teachers’ innovative behavior and thriving at work: A moderated mediation model - Li, Qiu; Liu, Minghui (Frontiers in Psychology, 2023)
In today's society, teachers are increasingly focused on the harmonious development of work and family. However, few studies have discussed family-supportive supervisor behavior to promote teachers' innovative behaviors and thriving at work. In this study, we adopt a questionnaire-based follow-up study of 409 career married teachers in Northwest China at three time points based on the Work-home Resource Model and Resource Conservation Theory. The study explores the mechanisms of family-supportive supervisor behaviors on teachers' innovative behaviors and thriving at work. The results indicate that family-supportive supervisor behavior has a significant positive predictive effect on teachers' innovative behavior and thriving at work, and work-family enrichment mediates between this relationship. In addition, proactive personality moderates the relationship between family-supportive supervisor behavior and work-family enrichment and the mediating role of work-family enrichment. That is, the higher the level of proactive personality, the stronger the effect of family-supportive supervisor behavior on teachers' innovative behavior and thriving at work and the mediating role of work-family enrichment.